Higher education for economic development: contexts of escaping low-and-lower-middle-income trap in ASEAN - Hara Masatoshi (Discover Education)
Abstract This study aims at the contribution of education to ASEAN low-and-lower-middle-income countries (LLMICs) economic development and particularly the role of higher education in avoiding the low-and-lower-middle-income trap (LLMIT). Panel data analysis indicates a positive relationship between GDP per capita and higher education enrollment, though with its full effect constrained by persistent skill mismatches and poor digital infrastructure. Besides the quantitative findings, qualitative findings derived from the grounded theory approach (GTA) uncover severe impediments and propose measures such as e-learning, spin-offs from universities, and stabilizing community networks. The result underlines the need for continuous investment in higher education combined with primary and secondary education development as the foundation for human capital formation. In nations such as Cambodia, Laos, Myanmar, the Philippines, and Vietnam, issues like low tertiary participation, increasing privatization, and digital divides continue to be high hurdles. To overcome them, governments need to introduce inclusive education policies and increase access to the internet. At the same time, institutions of higher learning are urged to promote more inclusiveness, implement global academic standards, and spur innovation through entrepreneurship led by universities.